Pengaruh Investasi, Tenaga Kerja, dan Indeks Pembangunan Manusia terhadap PDRB (Studi Kasus Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2016-2018) - Andre Budihardjo; Fitrie Arianti; Fuad Mas’ud (Universitas Diponegoro, 2020)
This research was conducted to determine the effect of investment, labor and human development index on the economic growth of districts and cities in Central Java. The data analysis model used to determine the relationship between variables is used panel data analysis. The analytical method used in this study is a quantitative descriptive analysis method through secondary data with data of 35 districts and cities in Central Java Province and the time series from 2016 to 2018. The results of the analysis of this study indicate that partially the investment variable has no effect on GRDP growth rate, labor variable has no effect on GRDP growth, and the human development index (HDI) variable has a positive effect andt affect GRDP growth in Central Java during the study period. While simultaneously investment variables, labor, human development index (HDI) affect the GRDP growth rate.